2013
DOI: 10.3389/fpsyt.2013.00118
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Biomarkers as Predictors and Correlates of Symptom Improvement Following Psychotherapy in Combat Veterans with PTSD

Abstract: Epigenetic alterations offer promise as diagnostic or prognostic markers, but it is not known whether these measures associate with, or predict, clinical state. These questions were addressed in a pilot study with combat veterans with PTSD to determine whether cytosine methylation in promoter regions of the glucocorticoid related NR3C1 and FKBP51 genes would predict or associate with treatment outcome. Veterans with PTSD received prolonged exposure (PE) psychotherapy, yielding responders (n = 8), defined by no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
227
2
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(265 citation statements)
references
References 61 publications
12
227
2
10
Order By: Relevance
“…Evidence suggests that the role of FKBP5 in the mammalian stress response includes epigenetic mechanisms such as DNA methylation status. Previous reports from the clinical literature have shown that methylation of the Fkbp5 gene (at the promoter region of exon 1) did not predict treatment response, but decreased in association with recovery (Yehuda et al, 2013). A study using a chronic corticosterone administration paradigm, that had been previously shown to result in a phenotype similar to chronic stress exposure (Gourley et al, 2009), induced an increase in Fkbp5 mRNA expression in the hippocampus, hypothalamus, and blood of mice with a correspondent decrease in DNA methylation at Fkbp5 intron 5 (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the role of FKBP5 in the mammalian stress response includes epigenetic mechanisms such as DNA methylation status. Previous reports from the clinical literature have shown that methylation of the Fkbp5 gene (at the promoter region of exon 1) did not predict treatment response, but decreased in association with recovery (Yehuda et al, 2013). A study using a chronic corticosterone administration paradigm, that had been previously shown to result in a phenotype similar to chronic stress exposure (Gourley et al, 2009), induced an increase in Fkbp5 mRNA expression in the hippocampus, hypothalamus, and blood of mice with a correspondent decrease in DNA methylation at Fkbp5 intron 5 (Lee et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Goals may be physical (e.g., nourishment, a safe home) or spiritual (e.g., dignity) but do not always have to be achieved completely [19]. Positive adaptation depends on personal traits, moderated by the environment [20,21]. As an outcome, someone feels more or less resilient [19].…”
Section: Resiliencementioning
confidence: 99%
“…The authors found that these changes in DNA methylation correlated with changes in cognitive functions. Yehuda et al (2013), in a pilot study, found that DNA methylation of the FKBP5 gene decreased during the course of psychotherapy of war veterans with PTSD. Roberts et al (2014) found in children with anxiety disorders that methylation of the promoter of the gene encoding the serotonin transporter (5HTT) increased in responders as compared to non-responders after the start of cognitive behaviour therapy.…”
Section: Role Of Epigenetics In Psychotherapymentioning
confidence: 99%